SIMULATION AND EXPERIMENTS ON SELECTING THE ECHO FREQUENCY IN DETECTING THE HEAT EXCHANGE TUBE FOULING - SUN LingFang; WANG TongTong; LI Xia; PIAO Heng (Jixie qiangdu, 2019)
The experiments under the coupling of the multi-physics field don’t have the conditions to be carried out in the heat exchange tubes fouling test. And it’s very important to establish the accurate ultrasonic propagation model for achieving the numerical simulation of selecting the detection frequency. Based on the finite element method,the three-dimension model with different heat exchange tubes had been established under the COMSOL Multiphysics condition. The varied relationship of the ultrasonic wave propagation,the different heat exchange tubes and echo exciting frequency were discussed respectively. The characteristic frequency and echo vibration mode of multi-layer tubes were found. The results show that the relationship between different characteristics of the heat exchange tubes（ material and wall thickness） and pressure load is similar. The ultrasonic time-domain reflectometry technology to detect the thickness of the tube fouling needs to select 5 MHz echo exciting frequency at least for inhibiting the pseudo-Gibbs oscillation. The optimal detection frequency is 10 MHz,and the detection effect is the best when the thickness at 3 mm ～ 5 mm. The numerical simulation agrees with the test results,and ultrasonic detection produces an error around ±5% in examining tube fouling deposit. These results provide a basis for quantitative detecting basis to select the characteristic frequency under the different tubes.